Separation and characterization of biosurfactant from P.aeruginosa sp1 isolated from oil mill area MIDC, Parbhani (M.S.) - Gujar, R S; Hamde, V S (International Multidisciplinary Research Journal, 2012)
Biosurfactant are an amphiphilic compound that reduces surface and interfacial tensions by accumulating at the interface of immiscible fluids and increase the surface areas of insoluble compounds leading to increased mobility. The extraction of the biosurfactant from the cell free supernatant using the solvent extraction procedure and the quantitative analysis has been discussed. The application of the biosurfactant includes biomedical, cosmetics and bioremediation rhamnolipid biosurfactant produced by Pseudomonas aeruginosa sp showed significant applications in the bioremediation of hydrocarbon in gasoline spilled oil and petroleum oily sludge in this review we discuss the potential roles and applications of biosurfactant, mainly focusing on areas such as food and food related industries, biomedicine and therapeutics.